1,4-Reduction of α,β-Unsaturated Ketones through Rhodium(III)-Catalyzed Transfer Hydrogenation - Yu, Xuewen; Wan, Saihong; Zhou, Wang (Synlett, 2022)
A rhodium(III)-catalyzed transfer hydrogenation of unsaturated ketones was developed. The simple catalytic system could be used for the 1,4-reduction of unsaturated cyclic, acyclic ketones, diketones, as well as β-ketoester, and a variety of functional groups were well-tolerated, affording products in moderate to excellent yields.
Keywords: 1,4-reduction; unsaturated ketone; rhodium(III) catalysis; transfer hydrogenation; isopropanol